Evaluation of Outflow Structures In Vivo after the Phacocanaloplasty - Daiva Paulaviciute-Baikstiene; Renata Vaiciuliene; Vytautas Jasinskas; Ingrida Januleviciene (Journal of Ophthalmology)
Purpose. To evaluate the in vivo changes in Schlemm’s canal (SC) and the trabecular meshwork (TM) in patients with primary open-angle glaucoma (POAG) after phacocanaloplasty using anterior segment optical coherence tomography (AS-OCT). Methods. Ten eyes of nine patients with POAG (6 men and 3 women) who underwent phacocanaloplasty. Preoperative and postoperative visual acuity (VA), intraocular pressure (IOP), and use of glaucoma medications were evaluated. The main outcome measures were the area of SC and TM thickness assessed using AS-OCT before and 12 months after surgery. Results. We found statistically significant reduction in IOP (from 26.4 (8.6) mmHg to 12.9 (2.5) (p<0.05) mmHg), increase in VA from 0.7 (0.4) to 0.9 (0.2), and decrease in glaucoma medication from 2.6 (1.2) to 1.1 (1.3) at 12 months postoperatively. There was a significant increase in the SC area (3081.7 (842.8) μm2 versus 5098.8 (1190.5) μm2, p<0.001) and a decrease in mean TM thickness (91.2 (18.6) μm versus 81.3 (15.1) μm, p=0.001) after surgery. We found negative correlations between SC area and IOP before surgery (r=-0.67, p=0.03) and also between SC area before and IOP reduction 12 months after the phacocanaloplasty (r=-0.80, p=0.005). Conclusions. Our results showed statistically significant dilation of SC area and reduction of TM thickness after phacocanaloplasty in POAG patients. The degree of SC expansion was related to the IOP decrease.